2015
DOI: 10.1590/s1677-5538.ibju.2014.0223
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Extraprostatic Disease According to the Percentage of Positive Biopsy Cores in Clinically Localized Prostate Cancer

Abstract: ObjectivePrediction of extraprostatic disease in clinically localized prostate cancer is relevant for treatment planning of the disease. The purpose of this study was to explore the usefulness of the percentage of positive biopsy cores to predict the chance of extraprostatic cancer.Materials and MethodsWe evaluated 1787 patients with localized prostate cancer submitted to radical prostatectomy. The percentage of positive cores in prostate biopsy was correlated with the pathologic outcome of the surgical specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The survival and prognosis of patients with extracapsular disease is less favorable compared to patients with localized disease confined to the prostate, highlighting the need for accurate methods of ECE detection [40]. Studies have shown that MRSI/mpMRI has improved the local staging of disease, including the detection of extracapsular spread of disease [41].…”
Section: Metabolic Imaging In Extracapsular Tumor Spreadmentioning
confidence: 99%
“…The survival and prognosis of patients with extracapsular disease is less favorable compared to patients with localized disease confined to the prostate, highlighting the need for accurate methods of ECE detection [40]. Studies have shown that MRSI/mpMRI has improved the local staging of disease, including the detection of extracapsular spread of disease [41].…”
Section: Metabolic Imaging In Extracapsular Tumor Spreadmentioning
confidence: 99%
“…In about 40 % of RC specimens, prostate cancer is incidentally detected of which approximately 20 % are clinically significant. Data on seminal vesicle involvement are scarce; however, in a recent trial in 24.5 % of radical prostatectomy specimen, extraprostatic disease (not necessarily into the seminal vesicles) has been found [33]. This high number has to be kept in mind if considering seminal vesicle sparing.…”
Section: Seminal Vesicle Sparingmentioning
confidence: 99%